2002
DOI: 10.1177/001698620204600206
|View full text |Cite
|
Sign up to set email alerts
|

Decisions Regarding Music Training: Parental Beliefs and Values

Abstract: Musical talent development generally involves high levels of parental support over an extended period of time. This study examined parents' expectancy beliefs and values regarding their child's music training, regular academic work, and athletic activities. Parents of 231 students, aged 6-18, who attended programs at four music institutions responded to a questionnaire. The results suggest that parents may initially send their children for music training not for musical talent development per se, but for more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 12 publications
1
23
0
3
Order By: Relevance
“…Similarly, other studies (e.g. Dai and Schader, 2002;Ilari 2013;Vincent and Ball 2007) have indicated that middle-class parents recognised that supporting their children's participation in enrichment activities such as music was an indicator of 'fundamental' and 'good' parenting skills.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Similarly, other studies (e.g. Dai and Schader, 2002;Ilari 2013;Vincent and Ball 2007) have indicated that middle-class parents recognised that supporting their children's participation in enrichment activities such as music was an indicator of 'fundamental' and 'good' parenting skills.…”
mentioning
confidence: 80%
“…Because formal musical activities demand not only financial resources and time investment, but a supportive home environment as well (Dai and Schader 2002), children's involvement in musical activities has often been considered a common practice of middle-class families (Vincent and Ball 2007). This idea is aligned with the concept of 'cultural capital' described by Pierre Bourdieu (1984), which refers to a series of strategies to manifest and reinforce one's position in a stratified social system through non-financial social assets.…”
mentioning
confidence: 99%
“…Further investigation of the mesosystem (e.g., interactions between parents and teachers) and exosystem (e.g., events or situations indirectly affecting the student) in regard to dance talent development is warranted because these factors might also be influential. In this study, it is plausible that these highly committed students matter-of-factly enjoy positive relationships with adults and, hence, an interesting topic for future research would be to examine any bidirectional relationship (i.e., direction of influence; Dai & Schader, 2002).…”
Section: Implications and Future Researchmentioning
confidence: 99%
“…Many researchers (e.g., Bloom, 1985;Ericsson 1996;Ericsson & Charness, 1994;Gagné, 1985Gagné, , 1995Walberg, 1992) have provided persuasive evidence of the significant contribution of environmental factors to TP. Such environmental inf luences include parenting (Campbell, 1996;Dai & Schader, 2002;Freeman, 1991Freeman, , 2003, schooling (Clark, 1992(Clark, , 2002Feldhusen, 1989;Rogers, 2002;VanTassel-Baska, 1992), peers (Biller & Kimpton, 1997;Bloom, 1985), interpersonal factors (Biggs, 1996;Fraser, Walberg, Welch, & Hattie, 1987), and the impact of specific training and practice (Allenbaugh, 2002;Ericsson & Charness, 1994;Ericsson, Krampe, & Tesch-Romer, 1993). This shift from nature to nurturing factors may be construed as a challenge to the traditional Western concepts of learning and performance, which has consequently led to a f lourishing of various theories and models concerning giftedness and TP.…”
Section: P U T T I N G T H E R E S E a R C H T O U S Ementioning
confidence: 99%